Utilizing Blockchain Technology to Increase Transparency in Education in Indonesia - Lasut, Meiske MW (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2025)
This study aims to analyze the potential, challenges, and opportunities for implementing blockchain technology to improve educational transparency in Indonesia. The method used is a qualitative approach with a literature review, involving searching scientific articles, books, and research reports through the Google Scholar database. Data analysis was conducted using thematic analysis techniques to identify patterns and meanings relevant to the Indonesian educational context. The results show that blockchain has significant potential to prevent academic document forgery, increase education budget transparency, and facilitate the implementation of digital credentials. However, significant challenges remain, including the lack of a clear legal framework, limited technological infrastructure in certain regions, and issues regarding student data privacy. The opportunity for blockchain implementation is wide open thanks to national policy support and the readiness of some educational institutions that have experimented with blockchain application prototypes. This study recommends that blockchain implementation be carried out in stages, accompanied by human resource training and strengthening regulations on personal data protection. These findings are expected to serve as a reference for policymakers and education practitioners in adopting blockchain technology to improve educational transparency and accountability in Indonesia.